2015
DOI: 10.1186/s13030-015-0044-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of anorexia nervosa in Japanese adolescents

Abstract: BackgroundNo epidemiologic survey examining eating disorders in Japan has been done at a national level since 1992. The prevalence of anorexia nervosa, as assessed by questionnaires to hospitals, is thought to be underestimated because patients with anorexia nervosa tend to avoid consultations. In conformity with the School Health and Safety Act of Japan, schools are required to have physicians perform a medical examination of students every year. The teachers in charge of health education and school physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…The most commonly used interview was the SCID (all SCID interview formats included), 12,99,100 applied in 9 (31.0%) out of 29 studies, closely followed by the EDE. Sample sized ranged from 93 92 to 252 838, 77 with the vast majority of studies (39 studies) presenting prevalence data on samples ranging in size from 1000 to 5000 participants. For the proportion of studies assessing ED prevalence using interviews only, nearly 50% (10 out of 22) of studies reported having used the WHO WMH-CIDI, 11 or modified versions of this instrument.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used interview was the SCID (all SCID interview formats included), 12,99,100 applied in 9 (31.0%) out of 29 studies, closely followed by the EDE. Sample sized ranged from 93 92 to 252 838, 77 with the vast majority of studies (39 studies) presenting prevalence data on samples ranging in size from 1000 to 5000 participants. For the proportion of studies assessing ED prevalence using interviews only, nearly 50% (10 out of 22) of studies reported having used the WHO WMH-CIDI, 11 or modified versions of this instrument.…”
Section: Data Collectionmentioning
confidence: 99%
“…13 Thirteen (24.5%) studies reported interviewing participants using [clinical] interviews based on DSM-IV criteria, without specifying details. The remaining 3 studies reported sample sizes ranging from between 30 000 to over 250,000 participants, the 2 two largest using either self-report (N 5 252,838), 77 or interview (N 5 100,000) 59 to assess ED prevalence. Eight of these 10 studies were American.…”
Section: Data Collectionmentioning
confidence: 99%
“…Only one study used interviews of 1,130 females by nursing teachers among 13 high schools in Japan, and the highest prevalence was reported (2.03% in 2002) [24]. The most recent survey has been published by Hotta et al [25] using a questionnaire to elementary, junior high, and senior high schools in seven prefectures. The point prevalence of AN for girls, including strongly suspected cases, in the three grades of junior high school and three grades of senior high school were 0-0.…”
Section: Prevalence Of An In Japanmentioning
confidence: 99%
“…Furthermore, the symptoms of AN in childhood are atypical, therefore this condition is often overlooked, and patients eventually visit the hospital only after it has become advanced. According to epidemiological research conducted in junior high and high schools, one‐third–one‐half of AN patients had not visited a doctor and had not received treatment …”
mentioning
confidence: 99%
“…According to epidemiological research conducted in junior high and high schools, one-thirdone-half of AN patients had not visited a doctor and had not received treatment. 15 To achieve early detection of difficult-to-find AN in children and adolescents, it is therefore important not to miss the initial signs. The first sign of AN is abnormal eating behavior based on fear of becoming fat, leading to a significant decrease in energy intake.…”
mentioning
confidence: 99%